IMPERFECTION IN EMMA S CHARACTER BASED ON JANE AUSTEN S EMMA - Mukin, Kristina; Liando, Nitha V. F.; Lolowang, Imelda S. (SoCul: International Journal of Research in Social Cultural Issues, 2022)
The purpose of this study is to investigate the imperfection of Emma s character in the novel Emma< em> by Jane Austen This research is qualitative research since the researcher collects data in the form of words quoted from the work itself to support the research This study used the feminist literary approach to explain the situation that occurred to Emma as a woman and how her character develops in that time as described in Jane Austen s novel Emma< em> The results of this study show that imperfection is part of Emma s character Jane Austen developed her most flawed protagonist within the confines of Emma Emma is imperfect due to her complexity and many more enticing things besides; her jealousness judgmental and selfishness < p>